Percutaneous tibial nerve stimulation versus sacral nerve stimulation for the treatment of faecal incontinence - O’Connor, Alexander; Reynolds, Elizabeth; Molyneux, Clare; Vasant, Dipesh H.; Sharma, Abhiram; Faulkner, Gemma; McLaughlin, John; Kiff, Edward; Telford, Karen (Frontiers in Surgery, 2024)
Faecal incontinence (FI) is a common condition with a significant impact on quality of life (QoL).Neuromodulation treatments delivered by members of the multidisciplinary team including sacral nerve stimulation (SNS) and percutaneous tibial nerve stimulation (PTNS) are options for FI refractory to conservative management. The aim of this study was to assess whether a successful treatment with one neuromodulation modality corresponds with success in the other.A retrospective review of a prospectively managed neuromodulation database identified 15 patients who had undergone both PTNS and SNS. The definition of success of each treatment was a >50% improvement in any of The St. Mark's Incontinence Score, Manchester Health Questionnaire, or weekly faecal urgency or FI episodes.Complete data from 12 patients was available for assessment and PTNS was delivered as the first treatment in nine patients. Overall, seven patients (58%) had successful PTNS treatment, with 10 (83%) having a successful SNS trials. Of the seven patients who had successful PTNS treatment, six patients (85.4%) went on to have success with SNS. Of the five patients who failed PTNS, four (80%) went on to have SNS success. Five (71%) of those who had positive PTNS outcomes had permanent SNS implantation as their final treatment decision.This study suggests that there is no clear relationship between successful PTNS treatment and an SNS trial period which may be explained by differing mechanisms of action or the potential placebo effect of PTNS. Further work is required to investigate any association in larger studies to inform clinical practice.